Synthesis, characterization and photocatalysis of BiOCl/BiPO4 composites - Wachiraporn Maisang (2020)
© 2020, Iranian Chemical Society. In this research, 0–20 wt% BiOCl/BiPO4 composites were synthesized from bismuth nitrate pentahydrate, disodium hydrogen phosphate dihydrate and different weight contents of potassium chloride by a one-step microwave-assisted hydrothermal method. The as-prepared samples were characterized by X-ray powder diffraction, scanning electron microscopy, transmission electron microscopy, Fourier-transform infrared spectroscopy, ultraviolet–visible (UV–visible) spectroscopy, photoluminescence spectroscopy and mass-to-charge (m/z) ratio spectroscopy. The products were composed of rod-shaped monoclinic BiPO4 and nanoplates of tetragonal BiOCl. The BiOCl/BiPO4 composites showed photocatalytic performance in the degradation of rhodamine B (RhB) solution under xenon visible radiation higher than pure single phase. In this research, 20 wt% BiOCl/BiPO4 composites showed photodegradation of RhB solution almost 100% within 30 min.